INQUIRY-BASED LEARNING IN PRIMARY SCHOOL MATHEMATICS: A SYSTEMATIC REVIEW OF ITS IMPACT ON STUDENT LEARNING OUTCOMES - Ashari, Nur Wahidin (Universitas Cokroaminoto Palopo, 2025)
The persistently low mathematics learning outcomes at the elementary level remain a critical issue in basic education. Traditional teacher-centered instructional approaches often fail to foster students’ conceptual understanding and critical thinking skills. This study aims to systematically analyze the effectiveness of the inquiry-based learning model in enhancing mathematics learning outcomes among elementary school students. A Systematic Literature Review (SLR) method was employed to identify, evaluate, and synthesize relevant studies published between 2015 and 2025. Literature was sourced from Google Scholar using strict inclusion criteria. The results indicate that the inquiry-based learning model has a significant positive effect on students’ mathematics achievement, particularly in improving conceptual understanding, problem-solving skills, and learning motivation. Variants of inquiry implementation—such as guided and open inquiry—were found to be effective in the context of elementary mathematics instruction. These findings highlight the importance of adopting inquiry-based learning as a pedagogical strategy to improve the quality of mathematics education at the primary level.